An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show - Difta Anggraini; Sudiran Sudiran (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show